2012
DOI: 10.1111/j.1748-1716.2012.02420.x
|View full text |Cite
|
Sign up to set email alerts
|

Early cardiac dysfunction is rescued by upregulation of SERCA2a pump activity in a rat model of metabolic syndrome

Abstract: In early stage, metabolic syndrome primarily disturbs SERCA2a function in the heart, but consequential haemodynamic dysfunction is prevented by upregulation of SERCA2a protein level and phosphorylation pathways regulating PLB. However, this compensated state is very vulnerable to a further decline in SERCA2a function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In contrast, in a rat model of obesity and IR induced by a diet including sucrose and condensed milk, it was found that decreased SERCA2a activity correlates with its low expression, as well as increased expression and decreased phosphorylation of PLN [89]. Miklos and coworkers using fructose-fed rats showed that despite a slowed decay of ES Ca 2+ transients and depressed SERCA2a function, expression of SERCA2a and PLN phosphorylation are increased [88]. Interestingly, they did not observe alterations in the function of isolated working hearts, thus suggesting that decreased SERCA2a activity may precede cardiac dysfunction and that increased expression of SERCA2a may represent a compensatory mechanism to prevent impaired cardiac function.…”
Section: Mechanisms Contributing To Diastolic Dysfunctionmentioning
confidence: 80%
See 1 more Smart Citation
“…In contrast, in a rat model of obesity and IR induced by a diet including sucrose and condensed milk, it was found that decreased SERCA2a activity correlates with its low expression, as well as increased expression and decreased phosphorylation of PLN [89]. Miklos and coworkers using fructose-fed rats showed that despite a slowed decay of ES Ca 2+ transients and depressed SERCA2a function, expression of SERCA2a and PLN phosphorylation are increased [88]. Interestingly, they did not observe alterations in the function of isolated working hearts, thus suggesting that decreased SERCA2a activity may precede cardiac dysfunction and that increased expression of SERCA2a may represent a compensatory mechanism to prevent impaired cardiac function.…”
Section: Mechanisms Contributing To Diastolic Dysfunctionmentioning
confidence: 80%
“…Impaired relaxation accompanied by a prolonged decay of electrically stimulated (ES) Ca 2+ transients in ventricular myocytes is an important feature of obesity and IR-related cardiomyopathy [15,16,48,50,52,85,88]. Therefore, the potential role of key proteins involved in cytosolic Ca 2+ removal (e.g., SERCA2a and NCX) has been of particular interest in finding a mechanistic explanation for impaired cardiac relaxation in obesity and IR.…”
Section: Mechanisms Contributing To Diastolic Dysfunctionmentioning
confidence: 98%
“…In contrast, there is considerable controversy regarding the amount of PLB, which has been reported to be increased in diabetes (Zhong et al 2003) and obesity (Relling et al 2006), decreased in obesity (Ceylan-Isik et al 2011), and preserved in hypertension (Boknik et al 2001), diabetes (Bai et al 2012;Basu et al 2009;Zhong et al 2003), heart failure (Sande et al 2002), and insulinresistance (Miklos et al 2012). In contrast, a decreased amount of Ser 16 -phosphorylated PLB has been widely shown in animal models of hypertension (Boknik et al 2001), diet-induced insulinresistance (Mellor et al 2012), obesity (Ceylan-Isik et al 2011), diabetes (Zhong et al 2003v;Rodrigues et al 2011), and heart failure (Sande et al 2002), while there have been few reports describing an increased phosphorylated PLB amount in dietinduced insulin resistance (Miklos et al 2012). Since PLB monomers negatively regulate Ca 2+ reuptake into the SR by SERCA and this process is reversed by phosphorylation at Ser 16 , decreased phosphorylated PLB amounts in SHRSP fatty rats may have important implications for regulation of SERCA by PLB, leading to the development of cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 90%
“…A decreased amount of SERCA2a in cardiomyocytes has been widely shown in many disease conditions, such as hypertension (Boknik et al 2001), obesity (Ceylan-Isik et al 2011), insulinresistance (Mellor et al 2012), and diabetes (Zhong et al 2003;Basu et al 2009;Rodrigues et al 2011;Bai et al 2012), while some studies have reported an enhanced amount in diet-induced insulinresistance and obesity (Relling et al 2006;Miklos et al 2012). In contrast, there is considerable controversy regarding the amount of PLB, which has been reported to be increased in diabetes (Zhong et al 2003) and obesity (Relling et al 2006), decreased in obesity (Ceylan-Isik et al 2011), and preserved in hypertension (Boknik et al 2001), diabetes (Bai et al 2012;Basu et al 2009;Zhong et al 2003), heart failure (Sande et al 2002), and insulinresistance (Miklos et al 2012).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation